Exact solution of unsteady MHD free convective flow with constant heat flux: revisited - Basant K. Jha; Luqman A. Azeez; Michael O Oni (Institute of Advanced Engineering and Science, 2021)
A solution of unstable MHD free convective flow of an incompressible, viscous and electrically steering fluid created by spontaneous motion of vertical plate subjected to constant heat fluctuation offered by Sacheti et al. has been revisited. The governing equations are deciphered with the aid of Laplace transform procedure, while the inversion is gotten through the Riemann sum approximation approach. Fluid velocity are varied with sundry parameters such as, Prandtl number, Grashof number and Hartmann number have been extensively explicated with the help of graphs. Numerical comparison is carried out and equated with the benchmark values reported in literature and an outstanding agreement is established. This article targeted at amending some discrepancies in the skin-friction offered by Sacheti et al. The benefit of the suggested technique could be a reduction of computation time.